Differentiation and identification of winter bread wheat verieties according to a complex of baking quality indicators - О. А. Демидов (Ukrainian Institute for Plant Variety Examination, 2021)
Purpose. Reveal the features of the formation of a quality indicator complex in winter bread wheat depending on the growing seasons, preceding crops and sowing dates, as well as differentiate and identify genotypes with high and stable levels of manifestation.